Forecasting the potential of Danish biogas production: spatial representation of Markov chains - Mikkel Bojesen; Hans Skov-Petersen; Morten Gylling (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2013)
This paper forecasts the spatial distribution of Danish husbandry production from 2009 until 2025. The study builds on a time series data set (1999 – 2009) for the number of livestock units (including piglets, finishers, sows, dairy cattle and young stock) measured by 1km2 grid cells for the whole of Denmark. A Markov Chain Model (MCM) was applied to estimate transition probabilities for the future livestock intensity composition, divided into state classes. Neighbouring effects between grid cells were not included. The modelled transition probabilities fit the data very well in all state classes, except for those farms which are in the largest state class. Regional differences in development trends were documented. The strategic objective of the model is to provide data for the spatial assessment of the potential of biogas production which can form the basis for a location analysis for future biogas plants.
Keywords: Q47; Q16; Q21; 330; structural changes; Markov Chain Models; biogas; agriculture